Scientific Manpower Allocation to New Drug Screening Programs - Pyle, E. B.; Douglas, B.; Ebright, G. W.; Westlake, W. J.; Bender, A. D. (Management Science, 1973)
A mathematical model has been developed for the purpose of assisting R&D management in the crucial task of allocating manpower resources to a set of competing pharmaceutical research programs. The problem is formulated such that the optimal manpower allocations among competing research programs are obtained through the use of a standard dynamic programming algorithm. A utility function is developed which allows for variations in the size, timing, and costs of the potential products from the various research programs. The model has been implemented on a digital computer, and the inputs and outputs are demonstrated through an example case. The model has been in existence for four years and is utilized quite extensively during the planning and budgeting cycles.